A Comparison between the Outcomes of Wound Closure by Primary and Secondary Healing after Mandibular 3rd Molar Impaction Surgery - Nayab Shad, Maryam Javed, Muhammad Saad Ui Hasan, Zafar Abbas, Sayyeda Tatheer Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The one of the most frequently performed procedure by the surgeon in the oral and maxillofacial surgeries is removal of mandibular third molar. Objective: The study aimed to compare the process of primary and secondary wound closure outcomes after the surgical removal of impacted mandibular third molar. Study design: It is a comparative study conducted at Armed Forces Institute of Dentistry, Rawalpindi for the duration of six months from Jan 2022 to June 2022. Material and Methods: The 65 patients visited the oral and maxillofacial surgery department of hospital were included in the study. According to the inclusion criteria, these patients had impacted their third molar and they were medically fit and ready to come for follow ups after the operation as well. The patients were divided into two groups. The group A had 33 patients, the average age of these patients was 30 years and proportion of male and female among these 33 patients was 40% male (13) and 60% female (20). Group B had 32 patients and among those 32 patients there were 46% male (14) and 53% female (18) and the average age of the participants was 27. Results: The percentage incidence of swelling and pain was higher in the group A. The values was statistically significant. The mouth opening was highly observed in the group B patients. The post-operative pain was measured at first day, third day and 7th day by making use of the visual analog scale. The comparison was made. The mean pain score on third day was 4.9 and 3.5 and on the seventh day the mean pain score was 3.2 and 1.5 respectively for group A and B. the overall variation in pain scores were significantly high. Conclusion: In this study, the conclusion is made that the secondary closure was a suitable option then the primary closure for the post-operative pain and swelling. There was no variation found in case of periodontal healing irrespective of the closure procedure used, but the risk of infection and food impaction is more in case of secondary closure. Therefore, if patients have poor hygiene conditions secondary closure is not suitable for them. Keywords: wound closure, healing type and mandibular third molar.